2017
DOI: 10.1371/journal.pone.0180779
|View full text |Cite
|
Sign up to set email alerts
|

Cystic nodal metastasis in patients with oropharyngeal squamous cell carcinoma receiving chemoradiotherapy: Relationship with human papillomavirus status and failure patterns

Abstract: ObjectivesWe investigated the relationships of cystic nodal metastasis, human papillomavirus (HPV) status, and treatment failure patterns in patients with oropharyngeal squamous cell carcinoma (OPSCC) treated with chemoradiotherapy.MethodsWe retrospectively reviewed pretreatment MRI and clinical courses of patients with OPSCC whose tumors were tested for HPV-induced p16 expression via immunohistochemistry and who completed chemoradiotherapy. Cervical cystic nodal metastasis and necrotic nodal metastasis were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 26 publications
1
29
0
1
Order By: Relevance
“…Before evaluation, the two neuroradiologists completed a training session with five patients to help them reach a consensus on evaluation of the imaging findings. Lymph nodes were considered as positive for radiologic ENE when at least one of the following criteria was met (92021222324): 1) enhancement, thickening, and irregularity of the nodal rim and 2) infiltration of the adjacent fat or other soft tissue planes (Fig. 2).…”
Section: Methodsmentioning
confidence: 99%
“…Before evaluation, the two neuroradiologists completed a training session with five patients to help them reach a consensus on evaluation of the imaging findings. Lymph nodes were considered as positive for radiologic ENE when at least one of the following criteria was met (92021222324): 1) enhancement, thickening, and irregularity of the nodal rim and 2) infiltration of the adjacent fat or other soft tissue planes (Fig. 2).…”
Section: Methodsmentioning
confidence: 99%
“…For primarily surgically treated cohorts it will be important in the future to identify risk factors in a prospective setting that are relevant for the patients’ prognosis because in Germany currently 75% of the OSCC patients undergo primary surgery. As an example, the cystic degenerated metastasis is mentioned, hereby poor local control rates after therapy without surgery are described 192 . In our own cohort, especially a young age could be identified as additional predictor for a good outcome of HPV OSCC patients 193 .…”
Section: Decision-making Tools For Therapymentioning
confidence: 99%
“…Für primär chirurgisch behandelte Kohorten wird es zukünftig bedeutsam sein auch in einem prospektiven Setting Risikofaktoren zu identifizieren, die für die Prognose der Patienten bedeutsam sind, denn in Deutschland werden aktuell 75% aller OSCC Patienten einer primär chirurgischen Therapie zugeführt. Beispielhaft kann die zystisch degenerierte Metastase angeführt werden, hier sind schlechte lokale Kontrollraten nach Therapie ohne Operation beschrieben 192 . In unserer eigenen Kohorte konnte für HPV OSCC insbesondere ein junges Lebensalter zusätzlich als Prädiktor für ein gutes outcome identifiziert werden 193 .…”
Section: 2 Welche Rolle Spielen Operationen?unclassified
“…The distinct oncogenesis of HPV-positive OPSCC results in characteristic histopathology 4 , 5 , perfusion, and diffusion parameters, which are related to the angiogenesis and cellularity of the tumour. Several studies have reported diagnosis of the HPV status in patients with OPSCC using preoperative computed tomography (CT) or magnetic resonance (MR) imaging 6 8 . HPV-positive OPSCC tends to exhibit cystic cervical lymph node metastasis 6 8 and primary tumours with well-defined borders and an exophytic appearance 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported diagnosis of the HPV status in patients with OPSCC using preoperative computed tomography (CT) or magnetic resonance (MR) imaging 6 8 . HPV-positive OPSCC tends to exhibit cystic cervical lymph node metastasis 6 8 and primary tumours with well-defined borders and an exophytic appearance 7 . Recent studies reported that diffusion-weighted imaging (DWI) may help predict HPV status in patients with OPSCC, as HPV-positive OPSCC reveals a low mean apparent diffusion coefficient (ADC) compared with HPV-negative OPSCC 9 11 .…”
Section: Introductionmentioning
confidence: 99%